2014
DOI: 10.1111/agec.12099
|View full text |Cite
|
Sign up to set email alerts
|

A roller coaster ride: an empirical investigation of the main drivers of the international wheat price

Abstract: Over the last decade, commodity prices have registered substantial booms and busts marked by extreme volatility. Wheat in particular, one of the main nonoil commodities, has registered a roller coaster in price levels which seems to be inconsistent with supply and demand fundamentals. To acutely investigate the drivers of wheat prices and quantify their impact, a vector error correction model (VECM) has been used. The exogenous variables have been distinguished into four groups: market-specific factors, broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…The estimated impulse response functions from FAVAR models are consistent, in terms of shape and magnitude, with those from similar studies that apply FAVAR in commodity price literature though our focus is different from theirs (Byrne et al., ; Lombardi et al., ). In the extended literature on commodity prices, our findings of the role of monetary policy are also consistent with the findings of Frankel () and Algieri () who emphasize the role of monetary policy in the long‐run development of commodity price.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The estimated impulse response functions from FAVAR models are consistent, in terms of shape and magnitude, with those from similar studies that apply FAVAR in commodity price literature though our focus is different from theirs (Byrne et al., ; Lombardi et al., ). In the extended literature on commodity prices, our findings of the role of monetary policy are also consistent with the findings of Frankel () and Algieri () who emphasize the role of monetary policy in the long‐run development of commodity price.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
“…() test the effects of monetary policy shocks on a broad index of commodity prices, and three indexes of metal, food and oil, and show that expansionary U.S. monetary policy shocks drive up the broad commodity price index and all of its components statistically significantly. To investigate the drivers of wheat prices, and quantify their impact, Algieri () estimates a VECM and demonstrates the long‐run cointegrated relationship between wheat price and four groups of variables, namely: market‐specific factors, broad macroeconomic determinants, speculative components, and weather. Scrimgeour () applying an event study method on 17 commodities (8 agricultural and 9 metals) shows that a surprise increase in interest rate reduces commodity prices immediately.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that grain prices positively react to anomalies in the El Niño-Southern Oscillation, which are linked to extreme weather events such as droughts (e.g. Algieri 2014, Ubilava 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence for a causal link between financial investment and commodity price dynamics has been mixed; see Irwin () and Cheng and Xiong (), for comprehensive literature reviews. Most empirical studies have focused on the impact of commodity indices on price levels and volatilities, such as Ott (), Sanders and Irwin (), and Algieri (, ). Few have looked at convergence, market basis, or term structure effects.…”
Section: Introductionmentioning
confidence: 99%